Barriers and Facilitators to Hypertension Control Following Participation in a Church-Based Hypertension Intervention Study. Issue 1 (January 2020) - Heinert, Sara; Escobar-Schulz, Sandra; Jackson, Maya; Del Rios, Marina; Kim, Sarah; Kahkejian, Jennica; Prendergast, Heather
Purpose: Hypertension is the primary risk factor for development of cardiovascular complications. Community-initiated interventions have proven effective in reducing cardiovascular disease risk among individuals who might otherwise face barriers to care. The purposes of this study were to gain feedback on a church-based hypertension intervention study and assess barriers and facilitators to hypertension control after participation in the study. Design: Qualitative study of 4 focus groups. Setting: Focus groups took place at 4 churches in primarily minority neighborhoods of Chicago, Illinois, in summer 2017. Participants: Thirty-one community members participated in the focus groups. Method: The Community Targeting of Uncontrolled Hypertension (CTOUCH) study was a church-based screening, brief intervention, and referral for treatment program for hypertension. Following the study completion, participants were invited to join a focus group to provide feedback on the study and discuss barriers and facilitators to hypertension control. The authors used the Framework Method to analyze the data. Results: Community Targeting of Uncontrolled Hypertension was well received by participants, particularly the awareness of their individual blood pressure and subsequent education on risk modification. The most common facilitators for hypertension control were social support, knowing how to control hypertension, and community resources. The most common barriers to hypertension control were lack of hypertension knowledge, negative primary care experiences, and lack of disease awareness. Conclusion: Knowledge of barriers and facilitators can inform areas of success and opportunities for improvement in community-based hypertension programs including future renditions in CTOUCH.